Faktor yang Mempengaruhi Keaktifan Kader Posyandu (Studi Di Puskesmas Bergas Kabupaten Semarang) - Heni Setyowati; Moneca Diah Listiyaningsih (Universitas Ngudi waluyo, 2018)
One of the efforts to realize a healthy society is to empower the community by involving community members or cadres willing to volunteer to engage in health issues. Posyandu is very dependent on the role of cadres. The activeness of these cadres is the determinant of the success of posyandu as the spearhead of health services. This research generally aims to analyze the factors that affect the activeness of posyandu cadres, so that can be used as a reference in determining the policy to be taken by Stakeholders. Specifically, the purpose of this research is to analyze the motivation of Posyandu cadres in implementing posyandu, to analyze the factors of reward system and to analyze the role of health workers to posyandu activities. This research was conducted at Puskesmas Bergas Kecamatan Bergas Kab Semarang by researching 50 cadres. In line with the objectives to be achieved in this research, which is analyzing the factors that influence the activeness of posyandu cadres, this study uses a corelative discriptive method. Data obtained then analyzed by descriptive analysis method and simple regression analysis using SPSS program. The results showed that there is a significant influence Motivation (X1), Awards (X2), and Performance Together Against the Activity of Posyandu Cadres at Puskesmas Bergas Semarang Regency. Suggestion It is expected that village midwives are more active in the implementation of posyandu and can do a good support to the cadre so that the cadre more spirit in the implementation Â Â posyandu.